Social media use by young Latin American consumers: An exploration. (July 2018) - Bailey, Ainsworth Anthony; Bonifield, Carolyn M.; Arias, Alejandro
Abstract: This paper reports on a study that was undertaken to explore the factors that drive social media use among young consumers in Latin America, a region of the world in which such studies have been sparse. The research involves the application of an extended TAM, with the addition of three new model variables whose impact on social media use have not been explored previously: social facilitation experience, fear of missing out (FoMO), and general online social interaction propensity (GOSIP). In addition, the outcome variable relates to active social media behaviors, a novel dependent variable in this stream of research. The model is tested using SEM. The results show that social influence, social facilitation experience, perceived ease of use (PEOU), and perceived enjoyment (PE) are all significantly linked to perceived usefulness (PU) of social media; however, FoMO is not. GOSIP, PU, and PE are positively related to attitude toward social media use, which is positively related to active social media behaviors. We discuss the results and provide limitations and avenues for future research.